Multi-Objective Design Optimization of the Reinforced Composite Roof in a Solar Vehicle - Ana Pavlovic; Davide Sintoni; Cristiano Fragassa; Giangiacomo Minak (Applied Sciences, 2020)
A multi-step and -objective design approach was used to optimize the photovoltaic roof in a multi-occupant racing vehicle. It permitted to select the best combination of design features (as shapes, widths, angles) in composite structures simultaneously balancing opposite requirements as static strength and dynamic stiffness. An attention to functional requirements, as weight, solar cells cooling and solar energy conversion, was also essential. Alternative carbon fiber-reinforced plastic structures were investigated by finite elements using static and modal analyses in the way to compare several design configurations in terms of natural frequencies, deformations, flexural stiffness, torsional stiffness, and heat exchange surfaces. A representative roof section was manufactured and tested for model validation. A significant improvement respect to the pre-existing solar roof was detected. The final configuration was manufactured and installed on the vehicle.